Constructing the world - Chalmers, David John, 1966- (Oxford : Oxford University Press, 2012)
David J. Chalmers constructs a highly ambitious and original picture of the world, from a few basic elements. He returns to Rudolf Carnap's attempt to do the same, and adopts the idea of scrutability - to address central themes in philosophy.
Includes bibliographical references (pages 475-483) and index.
Keywords: Knowledge, Theory of; Logical positivism